Epigenetic Modification in Oocyte and Preimplantation Embryonic Development - Yi-Xin Ren; William Chang; Jie Qiao (Reproductive and Developmental Medicine, 2017)
DNA methylation and histone modification are two of the most characterized epigenetic modifications. With advanced detecting techniques, particularly single-cell sequencing, we can dissect epigenomic patterns and their regulatory roles in the growth and differentiation of gametes and early embryos in animals and humans. Assisted reproductive technology (ART) procedures have been shown to influence the methylation of certain genes. Aberrant epigenetic regulation may cause several developmental disorders and clinical diseases. Here, we describe some concepts in epigenetics and review recent researches on DNA methylation and the histone modification profile and their regulatory roles during early embryo development. We also summarize the recent progress in understanding the imprinting disorders associated with ART procedures.